Self-Organising Electronic Institutions and Flexible Manufacturing Systems. Issue 3 (2015) - Sanderson, David; Ratchev, Svetan; Kelly, Emma; Busquets, Dídac; Pitt, Jeremy
Abstract: This paper addresses the issue of organised adaptation in flexible manufacturing systems using multi-agent systems and electronic institutions. We analyse two representative case studies, the first a reconfigurable manufacturing system for intelligent 'plug and produce', and the second an evolvable assembly system that changes over time as context and requirements change. We observe that the management of adaptation is typically the responsibility of intelligent agents operating in a multi-agent system, but that dealing with openness, selfdetermination or fulfilment and violation of contracts requires conventional, mutually-agreed and mutable rules. We therefore propose to use the computational framework of self-organising electronic institutions as one way to represent solutions to these problems. However, issues of scale, complexity and uncertainty also need to be addressed, and we discuss how the framework can be developed to address these research challenges. We conclude with some comments on the potential transformative impact of self-organising multi-agent systems on reconfigurable manufacturing and evolvable assembly systems.